Serum Trace Elements (Zinc, Copper and Magnesium) Status in Iraqi Patients with Acne Vulgaris :( Case- Controlled Study) - Basil OM Saleh; Zainab N. H. Anbar; Ali Y. Majid (College of Pharmacy University of Baghdad, 2017)
Recently on the dermatological fields, the serum levels and the roles of Zn, Cu and Mg have been studied especially in acne vulgaris, but the results were controversial. The aim of the present study is to investigate  a relationship between the severity of acne and the serum levels of zinc (Zn), copper (Cu) and magnesium (Mg) and to demonstrate the status of serum levels of zinc, copper, and magnesium in Iraqi male patients with acne vulgaris and to compare it with those of healthy controls.This case controlled study was conducted in the Department of Dermatology and Venerology and in the Poisoning Consultation Center of Baghdad Teaching Hospital between May 2009 to January 2010. Forty- five male patients with acne vulgaris, their ages ranged from 18-30 (21.82Â±3.77) years and 45 healthy male subjects as controls, their ages ranged from 18-30 (22.18Â±3.85) years were included in this study. Patients were subdivided into three groups according to the severity of their acne; mild acne group (n=15), moderate (n=15) and severe acne group (n=15). Investigations included serum estimation of Zn, Cu and Mg in both patient and control groups.The data obtained from this study showed that the (meanÂ±SD) values of serum levels of Zn was significantly decreased in severe acne group compared with controls, mild and moderate type of acne group (P< 0.05). Serum Mg concentration was significantly lower in severe acne group compared with mild and moderate acne group (P< 0.05). With regard to serum Cu, there were no significant differences  among groups of patients with acne vulgaris.This study revealed a significant association between serum levels of either Zn or Mg with the severity of acne. Key words: Acne vulgaris, zinc, copper, magnesium.